Chinese tourism consumption vis-à-vis tourism development strategies in the Arctic - Björner, Emma; Dybtsyna, Elena; Lundberg, Erik (2021)
The current national Arctic strategies of Sweden, Norway, and Finland consider tourism as a key industry and point out its significance for sustainable development in the region. Concurrently, China’s Arctic Policy talks about China being the source of tourists to the Arctic. Additionally, the tourism industry’s own strategies recognise that the Asian market shows strong growth in the number of travellers over the last decade. Further, there is great potential in the longer term. This chapter addresses how tourism development and destination branding is portrayed in policy and strategy documents dealing with the Arctic and how that corresponds with Chinese tourism consumption in the case of the Swedish Arctic. The findings show that, at all levels, tourism development and destination branding as portrayed in policies and strategies s increasingly tied to all three pillars of sustainability, even though economic and environmental aspects still dominate. Furthermore, relevant Chinese consumption patterns are elaborated upon. These patterns indicate that Chinese tourists are both similar to and different from Western travellers and have certain traits, partly influenced by cultural and Confucian values. Policies and strategy documents should be aligned with this notion in order to facilitate sustainable tourism development in the Arctic.